Effects of tiletamine-zolazepam vs. propofol on peri-induction intraocular pressure in dogs: A randomized, masked crossover study - McIver, Katharine A.; Boveland, Shannon D.; Clark-Price, Stuart C.; Hofmeister, Erik H. (Frontiers in Veterinary Science, 2023)
Introduction: Anesthesia induction agents have the potential to cause severe ocular side effects, resulting in lasting damage to the eye. Objectives: The purpose of this study is to determine the effects of tiletamine – zolazepam on IOP compared to propofol when they are used as an induction agent in normal healthy dogs. Methods: Twenty healthy adult client owned dogs weighing 22.2 ± 7.6 kg were selected for the study. In a randomized order, all dogs received tiletamine-zolazepam 5 mg/kg IV or propofol 8 mg/kg IV titrated to effect without premedication. Washout between each treatment was at least seven days. IOP measurements were obtained at four time points: baseline, post-induction, post-intubation, and after recovery using applanation tonometry. No additional procedures were performed. After normality of the data was determined, a linear mixed model was built with time, eye, treatment and all interactions of those variables as fixed effects and subject as a random effect. Results: There was no significant difference for age, body weight, drug dose, baseline IOP, and recovery IOP between treatments. Average IOP measurements remained within the normal range of 15-25 mmHg at these time points. However, IOP was significantly less elevated by the tiletamine-zolazepam treatment vs. propofol at the post-induction (mean difference: -4.7 ± 4.6 [95%CI -6.8 to -2.5]) and the post-intubation (mean difference: -4.4 ± 4.6 [95%CI -6.5 to -2.2]) time points. Clinical Significance: Dogs receiving tiletamine-zolazepam for anesthetic induction had a significantly less elevated IOP at induction and intubation compared to dogs receiving propofol.